Clinical Application of the Socket-Shield Concept in Multiple Anterior Teeth - G. Esteve-Pardo; L. Esteve-Colomina (Case Reports in Dentistry)
A case of rehabilitation of the upper front teeth is presented. To prevent bone resorption following extractions, a socket-shield technique on all the extracted teeth was performed. The combination of a staged extraction approach, the sequence of provisionals together with the minimal bone loss of vestibular volume, allowed solving this high aesthetic demanding case in a satisfactory way for the patient both in duration of the treatment and in its final outcome.